Evaluation of a global total water level model in the presence of radiational S2 tide. (December 2021) - Wang, Pengcheng; Bernier, Natacha B.; Thompson, Keith R.; Kodaira, Tsubasa
Abstract: The development of a computationally efficient scheme for predicting the global distribution of total water level (TWL) is discussed. The ocean model is barotropic, has a horizontal grid spacing of 1/12°, and is based on the NEMO modeling framework. It is forced by the gravitational potential and hourly atmospheric fields for 2008. Hourly time spacing was required to resolve the S 2  tide in global air pressure and wind. The predicted tide in water deeper than 400 m was nudged to TPXO8 "observations" of tidal elevation or current using a scheme called tidal nudging (Kodaira et al., 2019). The benefit of nudging horizontal velocity in the momentum equation, compared to sea level in the continuity equation, is discussed. Tidal nudging is shown to improve tidal predictions of sea level at the coast, particularly at the S 2  tidal frequency. The predicted radiational S 2  tide in sea level forced solely by the S 2  tide in global air pressure reaches amplitudes exceeding 80 cm. Decreasing the time spacing of the air pressure forcing from 1 h to 3 h reduces the S 2  amplitude in air pressure by a factor of 0.82, consistent with expectations based on Fourier analysis. This highlights the importance of using hourly atmospheric forcing when predicting the global sea level response to atmospheric forcing. The radiational S 2  tide in sea level is subject to strong nonlinear interaction with the gravitational tide, leading to a pronounced attenuation of the radiational S 2  tide. The attenuation is explained by an increase in effective bottom friction at the S 2  frequency due to the presence of the gravitational tide. Four schemes for predicting TWL are evaluated to quantify the impact of tidal nudging and nonlinear interaction of tide and surge. Using TWLs observed by 304 coastal tide gauges, we show it is necessary to include both tidal nudging and nonlinear interaction. Plans for the further development of an operational flood forecast system for the Canadian coast, based on the above model, are discussed. Highlights: A cost efficient scheme for predicting the global total water level is developed. Tidal nudging in deep water only is shown to improve tide prediction at the coast. Hourly atmospheric forcing is required to resolve the radiational S 2  tide (rS2 ). rS2  is subject to strong nonlinear interaction with the gravitational tide. It is necessary to use the coupled tide-surge model due to the nonlinear interaction.